An Attached Element and The Reception Theory. An Analysis of the Short Story “La siesta del martes” by Gabriel García Márquez - Padilla Villada, Edwin Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article analyzes the conversion of two poetics: The Reception Theory, according to Hans Roberts Jauss and the Attached Element, enunciated by Mario Vargas Llosa. In this analysis, the central question revolves around the relation that could exist between these two theories and the correspondence of the additions from the author and the de-codification from the attached element in order to have a successful reception. Therefore, this article studies the short story of La siesta del martes [1962] de Gabriel García Márquez (1927-2014) to find the links and understand overall the literary value and the universe of creation of the author which guarantee the reception of his work and his further perdurability.